Teaching and Learning Design and Technology : A Guide to Recent Research and Its Applications - Edited by Eggleston, John; Series Editor: Andrews, Richard (London Continuum, 2000)
A summary of research relating to the teaching and learning of technology and design in the classroom, relevant to the primary/elementary and the secondary/high school market. It covers the subject's teaching both as a separate subject and when integrated with other areas of the curriculum.
Include Figures and Index.
Keywords: Technology--Study and teaching -- Great Britain -- Industrial design--Study and teaching